Decoding Purchase Decisions: The Role of Influencer Credibility and Content - Ahyar Junaedi; Bayu Suratmoko; Nur Annisa; mohamad rafii rafii (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2026)
The rapid growth of social media has positioned influencer marketing as a key driver of consumer purchase decisions, yet the relative roles of influencer attributes and content characteristics remain unclear. This study investigates the effects of Influencer Credibility, Content Frequency, and Content Relevancy on Purchase Decision using survey data from 516 active social media users analyzed with SEM-PLS 4. The results show that the model explains 58.1% of the variance in Purchase Decision (R² = 0.581) and demonstrates strong predictive relevance (Q²predict = 0.570). Hypothesis testing indicates that Content Relevancy has a strong and significant effect on Purchase Decision (β = 0.613; t = 11.058; p < 0.001; f² = 0.370), making it the most influential predictor. Content Frequency has a positive but weak effect (β = 0.121; t = 2.192; p = 0.014; f² = 0.014), while Influencer Credibility does not significantly influence Purchase Decision (β = 0.080; t = 1.410; p = 0.079; f² = 0.008). These findings suggest that content relevance plays a more critical role than influencer credibility in shaping purchase decisions. The study highlights the importance of content strategy in enhancing the effectiveness of influencer marketing.